Alpha-Linolenic acid modulates phagocytosis and endosomal pathways of extracellular Tau in microglia - Desale, Smita Eknath; Chinnathambi, Subashchandrabose (Cell Adhesion & Migration, 2021)
Microglia, the resident immune cells, were found to be activated to inflammatory phenotype in Alzheimer's disease (AD). The extracellular burden of amyloid-beta plaques and Tau seed fabricate the activation of microglia. The seeding effect of extracellular Tau species is an emerging aspect to study about Tauopathies in AD. Tau seeds enhance the propagation of disease along with its contribution to microglia-mediated inflammation. The excessive neuroinflammation cumulatively hampers phagocytic function of microglia reducing the clearance of extracellular protein aggregates. Omega-3 fatty acids, especially docosahexaenoic acid and eicosapentaenoic acid, are recognized to induce anti-inflammatory phenotype of microglia. In addition to increased cytokine production, omega-3 fatty acids enhance phagocytic receptors expression in microglia. In this study, we have observed the phagocytosis of extracellular Tau in the presence of alpha-linolenic acid (ALA). The increased phagocytosis of extracellular Tau monomer and aggregates have been observed upon ALA exposure to microglia cells. After internalization, the degradation status of Tau has been studied with early and late endosomal markers Rab5 and Rab7. Further, the lysosome-mediated degradation of internalized Tau was studied with LAMP-2A, a lysosome marker. The enhanced migratory ability in the presence of ALA could be beneficial for microglia to access the target and clear it. The increased migration of microglia was found to induce the microtubule-organizing center repolarization. The data indicate that the dietary fatty acids ALA could significantly enhance phagocytosis and intracellular degradation of internalized Tau. Our results suggest that microglia could be influenced to reduce extracellular Tau seed with dietary fatty acids.
Keywords: alpha-linolenic acid; endosomal markers; Fatty acids; MTOC repolarization; Phagocytosis; Tauopathy

Phosphoinositides signaling modulates microglial actin remodeling and phagocytosis in Alzheimer's disease - Desale, Smita Eknath; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Alzheimer's disease is one of the neurodegenerative diseases, characterized by the accumulation of abnormal protein deposits, which disrupts signal transduction in neurons and other glia cells. The pathological protein in neurodegenerative diseases, Tau and amyloid-P contribute to the disrupted microglial signaling pathways, actin cytoskeleton, and cellular receptor expression. The important secondary messenger lipids i.e., phosphatidylinositols are largely affected by protein deposits of amyloid-beta in Alzheimer's disease. Phosphatidylinositols are the product of different phosphatidylinositol kinases and the state of phosphorylation at D3, D4, and D5 positions of inositol ring. Phosphatidylinositol 3,4,5-triphosphate (PI 3, 4, 5-P3) involves in phagocytic cup formation, cell polarization, whereas Phosphatidylinositol 4,5-bisphosphate (PI 4, 5-P2)-mediates the process of phagosomes formation and further its fusion with early endosome.. The necessary activation of actin-binding proteins such as Rac, WAVE complex, and ARP2/3 complex for the actin polymerization in the process of phagocytosis, migration is regulated and maintained by PI 3, 4, 5-P3 and PI 4, 5-P2. The ratio and types of fatty acid intake can influence the intracellular secondary lipid messengers along with the cellular content of phaphatidylcholine and phosphatidylethanolamine. The Amyloid-beta deposits and extracellular Tau seeds disrupt phosphatidylinositides level and actin cytoskeletal network that hamper microglial-signaling pathways in AD. We hypothesize that being a lipid species intracellular levels of phosphatidylinositol would be regulated by dietary fatty acids. Further we are interested to understand phosphoinositide-based signaling cascades in phagocytosis and actin remodeling.
Keywords: actin remodeling; Alzheimer's disease; Dietary fatty acids; Phagocytosis; Phosphoinositides; PI3K signaling